Simulation of a continuous fluidised bed dryer for shelled corn (Nexo Revista Científica, 2021)
In this study, a mathematical model to simulate the drying of shelled corn in a continuous plug-flow fluidised bed dryer is presented. Equipment and material models were applied to describe the process. The equipment model was based on the differential equations obtained by applying mass and energy balances to each element of the dryer. In the case of the material model, mass and heat transfer rates in a single isolated particle were considered. Calculation results were verified by comparison with experimental data from the literature. There was a very good agreement between experimental data and simulation. The effects of gas temperature and velocity, particle diameter, dry solid flow and solid temperature on the drying process were investigated. It was found that the changes in gas velocity, dry solids flow and the solid temperature had essentially no effect on the drying process.